Spatiotemporal profile of an optimal host response to virus infection in the primate central nervous system. - Olga A Maximova; Sarah L Anzick; Daniel E Sturdevant; Richard S Bennett; Lawrence J Faucette; Marisa St Claire; Stephen S Whitehead; Kishore Kanakabandi; Zong-Mei Sheng; Yongli Xiao; John C Kash; Jeffery K Taubenberger; et al. (PLoS Pathogens)
Viral infections of the central nervous system (CNS) are a major cause of morbidity largely due to lack of prevention and inadequate treatments. While mortality from viral CNS infections is significant, nearly two thirds of the patients survive. Thus, it is important to understand how the human CNS can successfully control virus infection and recover. Since it is not possible to study the human CNS throughout the course of viral infection at the cellular level, here we analyzed a non-lethal viral infection in the CNS of nonhuman primates (NHPs). We inoculated NHPs intracerebrally with a high dose of La Crosse virus (LACV), a bunyavirus that can infect neurons and cause encephalitis primarily in children, but with a very low (≤ 1%) mortality rate. To profile the CNS response to LACV infection, we used an integrative approach that was based on comprehensive analyses of (i) spatiotemporal dynamics of virus replication, (ii) identification of types of infected neurons, (iii) spatiotemporal transcriptomics, and (iv) morphological and functional changes in CNS intrinsic and extrinsic cells. We identified the location, timing, and functional repertoire of optimal transcriptional and translational regulation of the primate CNS in response to virus infection of neurons. These CNS responses involved a well-coordinated spatiotemporal interplay between astrocytes, lymphocytes, microglia, and CNS-border macrophages. Our findings suggest a multifaceted program governing an optimal CNS response to virus infection with specific events coordinated in space and time. This allowed the CNS to successfully control the infection by rapidly clearing the virus from infected neurons, mitigate damage to neurophysiology, activate and terminate immune responses in a timely manner, resolve inflammation, restore homeostasis, and initiate tissue repair. An increased understanding of these processes may provide new therapeutic opportunities to improve outcomes of viral CNS diseases in humans.